"Association of APOE gene polymorphisms with primary open angle glaucoma in Brazilian patients". (2nd January 2021) - Occhiutto, Marcelo Luís; de Melo, Mônica Barbosa; Cabral de Vasconcellos, José Paulo; Rodrigues, Thiago Adalton Rosa; Bajano, Flávia Fialho; Costa, Fernando Ferreira; Costa, Vital Paulino
ABSTRACT: Background : Primary open-angle glaucoma (POAG) is a multifactorial disease that affects 65.5 million people worldwide. In addition to the genetic variants already established as indicators of greater risk for POAG, the apolipoprotein ( APOE ) gene has been studied in some populations, with controversial results. The aim of this study is to investigate the frequency of the genetic variants of APOE in the Brazilian population, and to evaluate the association between these polymorphisms and the risk of POAG. Methods : APOE variants (rs429358; rs7412) were genotyped in 402 POAG patients and 401 controls. We evaluated the association between APOE genetic variants and the risk for POAG, as well as the correlation between the requirement of glaucoma surgery and the APOE polymorphisms. Results : Among the three APOE gene isoforms, we found a low frequency of APOE alleles ε2 (7.34%) and ε4 (11.76%), but a high frequency of ε3 (80.88%) in our population. When compared to ε3ε3 reference genotype, ε2 allele-carriers (OR = 1.516; p -value = 0.04) and ε2ε3 genotype (OR = 1.655; p -value = 0.02) were associated with a greater risk for POAG. An additive genetic model confirmed the influence of the ε2 allele in the risk of POAG in this sample of the Brazilian population (OR = 1.502; p -value = 0.04). There was no significant association between the analyzed genotypes and the requirement or number of glaucoma surgeries ( p > .05). Conclusion : Brazilian individuals carrying the APOE ε2 allele may be at an increased risk for the development of POAG.